DETERMINANTS OF DOMESTIC TOURIST EXPENDITURE IN BANYUWANGI - Adicayana, Febri Suci (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
In period of global economic downturn that effect to declining productivities of many sector in Banyuwangi. Actually, tourism raise as one sector that show positive trend. Domestic tourist continuously coming and consuming tourism product become new income generated for economy of Banyuwangi. This study aims to know what are determinant of Tourist Expenditure in term of domestic tourist who have visited Banyuwangi. So, the study used online survey method to tourist who have traveled to Banyuwangi. There were 120 respondents who participated. The survey data were analyzed using Partial Least Square (PLS).The results indicate that in variable of economic constraint only income that influence to tourist expenditure. Besides, only prices of tourism product, tourism facilities, ease of access, and public transport are become representative of travel-related characteristics variable. Then, travel experience, motivation and tpurism lifestyle are reflective of psychographics characteristic variable. Travel-related and psychographic are higher effect to tourist expenditure. In the other hand, socio-economic characteristics variable is not effect to the tourist expenditure.Keywords: Tourist Expenditure, Domestic Tourist, Banyuwangi,